PENGEMBANGAN VIDEO WAYANG JĀTAKA SEBAGAI MEDIA PEMBELAJARAN SISWA ADI SEKHA SEKOLAH MINGGU BUDDHA ADHICITTA - Wijayanto, Gustriya; Sukodoyo, Sukodoyo; Endah Ekowati, Wilis Rengganiasih (Jurnal Pencerahan, 2021)
This study aims to determine the process of making and the effectiveness of the Jātaka puppet video as a learning medium for Adhi Sekha (early children education) students at Adhicitta Buddhist Sunday School (BSS). The method used in this research is Research and Development using the ADDIE approach (Analyze, Design, Development, Implementation, Evaluation). Data collection techniques used include observation, interviews, questionnaires, and documentation. Data credibility is assessed by transferability, dependability, confirmability, and logical validity. Data analysis techniques used for qualitative data are reduction, presentation, and conclusion. Meanwhile, the quantitative data were analyzed by using descriptive percentage theory. Based on the results of the product feasibility assessment from the experts, the Jātaka puppet video got a feasibility percentage of 89% from material experts and 91.5% from puppet experts. The responses from BSS teachers and students were also very good when field trials were conducted. With this percentage, it can be said that the Jātaka puppet video media is appropriate to be used as a medium for BSS learning at the ECE level at Adhicitta Buddhist Sunday School.